A Contrastive Study of Shell Noun Use in English and Chinese Academic Articles - Liang Xiaorui (International Journal of Education and Humanities, 2024)
A shell noun (SN) is a type of abstract noun whose pragmatic meaning is encapsulated within the context. The term "shell" suggests its capability to encapsulate and convey information. Previous studies have focused primarily on the textual and interpersonal functions of SNs, often neglecting the comparative analysis of shell noun usage in Chinese and English discourses. To address this gap, this study conducts a comparative analysis of the use of SNs in English and Chinese based on a self-established corpus comprising three groups: 30 Chinese research papers written by Chinese scholars from Foreign Language Teaching and Research (外语教学与研究), 30 English research papers written by Chinese scholars, and 30 English research papers written by native English scholars from Studies in Second Language Acquisition over the past five years. The results are analyzed in terms of the overall distribution of SNs, the structural distribution of shell noun patterns, high-frequency SNs, and the category distribution of SNs. The findings reveal a similarity in the use of SNs by Chinese scholars in their Chinese and English papers, while there is a significant difference in the use of SNs between Chinese scholars and native English scholars in English articles